Tadpole morphology of Leptodactylus plaumanni (Anura: Leptodactylidae), with comments on the phylogenetic significance of larval characters in Leptodactylus - Grosso, Jimena R. (2015)
In this paper I summarize the morphology of the Leptodactylus plaumanni tadpoles, describing the external morphology, buccal cavity, and cranial skeleton and associated muscles. A distinctive combination of traits include the truncated snout in dorsal view, dorsal fin originated anterior to the body-tail junction, submarginal papillae present in some specimens, two slight indentations in the lower lip, ceratobranchial III free from the hypobranchial plate, small ventrolateral projections of the corpus of the suprarostral cartilage, m. subarcualis rectus I with three heads, and m. subarcualis rectus II-IV inserting in ceratobranchial I and connective tissue between branchial processes II and III. The buccal cavity shares the typical features in species of the group, namely four lingual papillae, two pairs of infralabial papillae, two postnarial papillae, and one pair of not branched lateral ridge papillae. Attending to the increasing role of larval characters in phylogenetic analyses, further research is needed to understand the evolution of tadpole morphology in this genus.